Daytime sleepiness predicts inflammation and ambulatory blood pressure in sleep apnoea. Issue 4 (26th October 2020) - Pak, Victoria M.; Butts, Brittany; Hertzberg, Vicki; Collop, Nancy; Quyyumi, Arshed A.; Cox, John; Rogers, Ann; Dunbar, Sandra B.
Introduction: Sleepiness in obstructive sleep apnoea is associated with cardiovascular risk; however, the biological mechanisms are not known. This study explored whether those with subjective sleepiness have increased plasma tumour necrosis factor-related protein 1 (C1qTNF1), a novel adipose-derived hormone (adipokine), and 24-h ambulatory blood pressure (ABP) compared to those without sleepiness in newly diagnosed, treatment-naïve participants with obstructive sleep apnoea. Methods: Overall, 94 participants were included in the analysis. Participants completed the Epworth Sleepiness Scale (ESS), 24-h ABP was monitored, and plasma C1qTNF1 was measured. Sleepy participants were defined as ESS≥10 and nonsleepy as ESS<10. Multiple linear regression was used to explore differences in C1qTNF1, and 24-h mean arterial pressure (MAP) between sleepy and nonsleepy participants, adjusting for age, sex, body mass index, apnoea–hypopnoea index, and smoking status. Results: C1qTNF1 was significantly higher in sleepy participants (n=57) compared to nonsleepy participants (n=37) (β=0.41 NPX, 95% CI 0.02, 0.80; p=0.04). The 24-h MAP was significantly higher in sleepy participants compared to nonsleepy participants (β=4.06 mmHg, 95% CI 0.36, 7.77; p=0.03). Conclusions: Our findings show that sleepiness is associated with inflammation and higher 24-h MAP in sleep apnoea. Excessive sleepiness experienced by treatment-naïve patients with obstructive sleep apnoea is associated with inflammation, higher daily systolic ambulatory blood pressure and higher 24 h mean arterial pressure https://bit.ly/3goeqGD